NAVIGATING MULTIPLE SHAREHOLDER STRUCTURES: STRATEGIC IMPLICATIONS FOR CORPORATE FINANCE - Nurul, Fadzlin Binti Mohd Noor; Muhammad , Faisal bin Mohd Yasin (Ayden Journal of Management and Social Sciences, 2025)
Numerous studies have examined the dynamics of multiple shareholders in firms, primarily focusing on aspects of firm performance and value, as evidenced by seminal works such as Lehmann and Weigand (2000), Gutierrez et al. (2003), Gutierrez et al. (2004), Maury (2004), Laeven and Levine (2008), and Attiq, Ghoul, and Guedhami (2009), among others. Additionally, a subset of literature has delved into the intricate relationship between large shareholders and firm policies, as explored by Cronqvist and Fahlenbrach (2007), Ghachem (2008), and Attiq et al. (2008). However, there remains a notable gap in the literature regarding the nuanced interplay between multiple shareholders, firm performance, and firm policies. This study seeks to address this gap by examining the multifaceted dynamics among multiple shareholders, firm performance metrics, and the formulation and implementation of firm policies. By employing a comprehensive analytical framework, this research aims to shed light on the intricate mechanisms through which multiple shareholders influence both the financial and strategic dimensions of firms